Mechanical Evaluation of Casing in Multiple Thermal Recovery Cycles for Offshore Heavy Oil Wells - Yuxian He; Yongpeng Song; Shenghua Hu; Hangming Liu; Xianchi Ge (Journal of Marine Science and Engineering)
China’s offshore heavy oil resources are abundant but underutilized. Circulating steam stimulation enhances production while increasing casing failure risks in thermal recovery wells. Accurately assessing casing performance after repeated thermal cycles is crucial for ensuring wellbore integrity. This paper presents tensile and creep experiments on TP110H casing under cyclic temperatures. The temperature distribution within the “casing-cement sheath-stratum” system is derived using heat transfer theory. Stress and displacement equations are established based on thick-walled cylinder theory and thermo-elasticity. Thermal coupling analysis assesses casing stress in straight, inclined, and sidetrack well sections. Key factors, including steam injection pressure, in situ stress, cement modulus, and prestress, are analyzed for their effects on cumulative strain below the packer. Strain-based methods evaluate casing safety. Results show that under thermal cycling at 350 °C, after 16 cycles, the casing’s elastic modulus, yield strength, and tensile strength decrease by 15.3%, 13.1%, and 10.1%, respectively, while the creep rate increases by 16.0%. Above the packer, the casing remains safe, but the lower section may be at risk. Using low-elasticity cement, higher steam injection pressure, and prestressing can help improve casing performance. This study provides guidance on enhancing casing safety and optimizing steam stimulation parameters.